Iowa Birdline update, September 14, 1992 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1992)
Email for the Iowa Birdline update for September 14, 1992. Highlights of the update include sightings from the fall IOU meeting, a Black-throated Blue Warbler, Cape May Warbler, American White Pelicans and a good number of raptors, especially Ospreys and Accipiters. Also included are handwritten notes for the next week's update with sightings of a Le Conte's Sparrow, Nelson's Sharp-tailed Sparrow and a Yellow Rail. Epson - sheet feed/flatbed